The origin of musculocutaneous nerve from median nerve: a case report - Agrawal, Soujanya; Singroha, Ritu; Rathee , Suresh Kantha (International Journal of Research in Medical Sciences, 2024)
The musculocutaneous (C5-C7) is the main nerve supplying muscles of the front of the arm, i.e., the coracobrachialis both the long and the short heads of biceps brachii and the brachialis muscles, and continues as the lateral cutaneous nerve of forearm 2 cm above the elbow joint. Usually, its origin is from the lateral cord of the brachial plexus, at the pectoralis minor’s lower border in the axilla. In regular dissection Bilateral variation in the origin of musculocutaneous nerve and lateral cutaneous nerve of the forearm was observed in a male cadaver. Both the musculocutaneous nerve and lateral cutaneous nerve of the forearm were found to be originating from the median nerve by a common stem. The nerve supply of muscles of the anterior compartment of the arm showed no variation. The present case was a rare anomaly and was being reported as this knowledge was of importance for surgeons, anesthetists and orthopedicians for anesthetic and other procedures.